REVIEW: EFEK EMISI AKUSTIK UNTUK MENDETEKSI KERUSAKAN DALAM PIPA - Ryan Syuhada; Feblil Huda (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Pipelines are vital elements in the oil and gas infrastructure, and damage to them can have serious consequences. This article aims to determine or study the basic concepts of acoustic emissions, damage detection principles, and their practical applications in industries that are closely related to pipeline systems. The methodology used in this article is a literature review. The result is that the acoustic emission method has advantages including its ability to detect damage at an accurate early stage, minimize downtime, and reduce maintenance costs. However, acoustic emission has several disadvantages such as, accuracy is greatly affected by environmental changes and external signal interference. The sensors used in acoustic emission are also very expensive. Overall, acoustic emission is a very effective method to detect damage in pipelines, the weaknesses contained in it are a challenge for future researchers.